KEWIRAUSAHAAN, INOVASI TEKNOLOGI, DAN KEUNGGULAN BERSAING PADA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) MAKANAN DI KECAMATAN CIBINONG - Luhung Bagas Prayogo; Suharyati Suharyati; M.B Nani Ariani (Universitas Pakuan, 2020)
This research is a quantitative research that aims to determine the effect of entrepreneurship and technological innovation on the competitive advantage of food MSMEs in Cibinong Subdistrict. The population used for this research is the businessmen MSMEs food entreprises at Cibinong Subdistrict. The number of sample which is taken was 50 respondents. The sampling technique for this research is purposive sampling method. The analysis technique used is Partial Least Square with 5% significance. The results of the testing are obtained (1) there is a significant effect of entrepreneurship on competitive advantage, (2) there is a significant influence of technological innovation on competitive advantage